PQM130, a Novel Feruloyl–Donepezil Hybrid Compound, Effectively Ameliorates the Cognitive Impairments and Pathology in a Mouse Model of Alzheimer’s Disease - Morroni, Fabiana; Sita, Giulia; Graziosi, Agnese; Ravegnini, Gloria; Molteni, Raffaella; Paladini, Maria Serena; Dias, Kris Simone Tranches; dos Santos, Ariele Faria; Viegas, Claudio; Camps, Ihosvany; Pruccoli, Letizia; Tarozzi, Andrea; et al. (Frontiers in Pharmacology, 2019)
Alzheimer’s disease (AD) is the most frequent type of dementia in older people. The complex nature of AD calls for the development of multitarget agents addressing key pathogenic processes. Donepezil, an acetylcholinesterase inhibitor, is a first-line acetylcholinesterase inhibitor used for the treatment of AD. Although several studies have demonstrated the symptomatic efficacy of donepezil treatment in AD patients, the possible effects of donepezil on the AD process are not yet known. In this study, a novel feruloyl–donepezil hybrid compound (PQM130) was synthesized and evaluated as a multitarget drug candidate against the neurotoxicity induced by Aβ1-42 oligomer (AβO) injection in mice. Interestingly, PQM130 had already shown anti-inflammatory activity in different in vivo models and neuroprotective activity in human neuronal cells. The intracerebroventricular (i.c.v.) injection of AβO in mice caused the increase of memory impairment, oxidative stress, neurodegeneration, and neuroinflammation. Instead, PQM130 (0.5–1 mg/kg) treatment after the i.c.v. AβO injection reduced oxidative damage and neuroinflammation and induced cell survival and protein synthesis through the modulation of glycogen synthase kinase 3β (GSK3β) and extracellular signal–regulated kinases (ERK1/2). Moreover, PQM130 increased brain plasticity and protected mice against the decline in spatial cognition. Even more interesting is that PQM130 modulated different pathways compared to donepezil, and it is much more effective in counteracting AβO damage. Therefore, our findings highlighted that PQM130 is a potent multi-functional agent against AD and could act as a promising neuroprotective compound for anti-AD drug development.